Some aspect of the intellectual trends in Malay literature from 1945-1960, with particular emphasis on cerpen and sajak. - Muhd Yusof Ibrahim, (Universiti Kebangsaan Malaysia, 1976)
The period between 1945-1960, was a turbulent one for West Malaysia (or Malaya then). In the beginning, there was the immediate after effect of the Japanese Occupation, and this was followed by other developments like the British political attempt to impose the Malayan Union, the communist insurgence which led to the Emergency, the struggle for independence and the independence itself. Such historical events, occurring within the period concerned, did not fail to attract the attention of the Malay intellectuals; some got themselves directly involved, while others just became "fence-sitters," In both cases modern Malay literature was turned into a very viable media as well as a platform for exposing, popularising and profounding one's political, economic and social ideas. As such literature almost became the only channel through which Malay intellectualism was displayed. Literature also almost became nothing more than a means towards a certain end. But in time it somehow managed to break away from such tendencies.